Uniaxial deformation of polystyrene–silica nanocomposites studied by hybrid molecular dynamics–finite element simulations - Liu, Shengyuan; Pfaller, Sebastian; Rahimi, Mohammad; Possart, Gunnar; Steinmann, Paul; Böhm, Michael C.; Müller-Plathe, Florian (Computational Materials Science, 2016)
This contribution investigates, based on molecular dynamics (MD), the mechanical deformation behavior of polystyrene-silica nanocomposites and focuses on the influence of  micromechanical properties as e.g. filler particle size and filler mass fraction. With regard to simulations of macroscopic problems with system sizes not capable by pure MD approaches, our investigations are complemented by hybrid molecular dynamics – finite element (MD-FE) simulations. Our computational approach shows show that an increasing total interfacial area between the nanoparticles and the polymer matrix stiffens the nanocomposite. As expected, small nanoparticles have more significant impact on the macroscopic mechanical properties of nanocomposites than large ones. We show that, for the same mass fraction of nanoparticles, the Young’s modulus increases by about 4–5% when the nanoparticle diameter is decreased from 5 to 2 nm. Furthermore, we find that: (i) the end-to-end distances of free polymer chains in the vicinity of nanoparticles are larger than in the bulk; (ii) the addition of nanoparticles slows down the global dynamics of free polymer chains; and (iii) the interphase thickness of nanocomposites is about 1–1.5 nm. Beyond that, we study structural properties at the microscale under uniaxial tension and find that the presence of nanoparticles hinders the orientation of free polymer chains under deformation. This hindrance is more pronounced for small nanoparticles and high mass fractions. Polymer structural descriptors as the chain end-to-end vector and a molecular anisotropy parameter largely change in line with the geometrical transformation of the whole sample.
Keywords: Polymer nanocomposites; Deformation; Hybrid particle-continuum approach; Molecular dynamics; Finite element